2017
DOI: 10.1080/2162402x.2017.1292195
|View full text |Cite
|
Sign up to set email alerts
|

LYG1 exerts antitumor function through promoting the activation, proliferation, and function of CD4+ T cells

Abstract: Identification of novel stimulatory cytokines with antitumor function would have great value in tumor immunotherapy investigations. Here, we report LYG1 (Lysozyme G-like 1) identified through the strategy of Immunogenomics as a novel classical secretory protein with tumor-inhibiting function. LYG1 recombinant protein (rhLYG1) could significantly suppress the growth of B16 tumors in WT B6 mice, but not in SCID-beige mice, Rag1 ¡/¡ mice, CD4 C -or CD8 C T cell-deleted mice. It could increase the number of CD4C a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…To obtain sufficient recombinant protein with high quality, CTRP4 was stably overexpressed in CHO cells via transfection of pcDNA3.1‐B‐CTRP4 as previously described [37]. Supernatants were collected and purified by affinity chromatography using Ni‐Sepharose 6 Fast Flow column (GE Healthcare, 11–0008).…”
Section: Methodsmentioning
confidence: 99%
“…To obtain sufficient recombinant protein with high quality, CTRP4 was stably overexpressed in CHO cells via transfection of pcDNA3.1‐B‐CTRP4 as previously described [37]. Supernatants were collected and purified by affinity chromatography using Ni‐Sepharose 6 Fast Flow column (GE Healthcare, 11–0008).…”
Section: Methodsmentioning
confidence: 99%
“…CXCL9, CXCL10-CXCR3 interactions has been linked to activated T cell trafficking to aGVHD target organs in humans and mice ( 16 ). Our previous study found that rhLYG1 administration in mice can enhance the expression of T cell chemokines, including CCL5, CXCL9 and CXCL10, and infiltration of T cells in tumors ( 11 ). In this study, the decreased infiltration of allogeneic CD4 + T cells in the livers and lungs of mice that received Lyg1 -/- T cells, which maybe related that LYG1 deficiency inhibited the expression of CXCL9 and CXCL10, explained partially that LYG1 deficiency in donor T cells suppressed aGVHD.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous injection of IL-12 or IL-18 increased the expression of IFN-γ, thereby inducing the expression of Fas in donor T cells, leading to activation-induc,ed cell death, reducing donor T cells responses to host antigens and finally attenuating aGVHD ( 26 , 27 ). Our previous studies have shown that rhLYG1 can promote antigen specific activity and IFN-γ production of T lymphocytes in tumor models ( 11 ). In this study, we found inhibited activation of CD4 + T cells and IFN-γ expression of allogeneic T cells in mice receiving Lyg1 -/- donor T cells, whereas rhLYG1 administration aggravated aGVHD severity through promoting IFN-γ production of allogeneic T cells, more importantly, the absence of IFN-γ in donor T cells could partially abrogate rhLYG1-induced GVHD development, corroborating that the effect of LYG1 on aGVHD were mainly mediated by IFN-γ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the spectrum of the enzyme's antibacterial activity can be significantly expanded as a result of modifications leading to changes in the protein structure that cause its oligomerization and an increase in surface hydrophobicity 3 , 4 . The modified lysozyme also has antiviral 5 and antifungal 6 , 7 properties and stimulates the appropriate cells of the body to produce various bioactive compounds to obtain antitumour activity 4 , 8 . According to the latest reports, by stimulating the formation of interferon-β 4 , the enzyme may be an effective agent against the SARS-Cov-2 virus and thus help fight COVID-19 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%